Bahasa Inggris - Moh Slamet Untung (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2020)
This study tries to describe the policy implemented by the Japanese fascist military authority toward pesantren education during their occupation in Indonesia. The research problem is how the policies used by the Japanese fascist military authority towards pesantren during their occupation in Indonesia before the independence of Indonesia. Primary data sources of this study include some works examining the policies of the Japanese fascist military authority towards pesantren education. Various scientific papers on Japanese colonization in Indonesia are used as secondary data sources of this study. This study uses historical approach and library research method focusing on the policies of the Japanese fascist military authority towards pesantren education. The collected data then were analyzed by using content analysis. This study exposes that the Japanese government provide more freedom for pesantren education than the Dutch colonial to develop themselves without any affection from the Japanese government. It could be seen from a fact that when pesantren were about to develop their basic potential as an educational institution teaching anti-colonial attitudes, Japanese government immediately acted repressively. They always monitored the kiai as well as all pesantren’s activities.